2019
DOI: 10.1038/s41467-019-09156-3
|View full text |Cite
|
Sign up to set email alerts
|

The development of synaptic transmission is time-locked to early social behaviors in rats

Abstract: The development of functional synapses is a sequential process preserved across many brain areas. Here, we show that glutamatergic postsynaptic currents anticipated GABAergic currents in Layer II/III of the rat neocortex, in contrast to the pattern described for other brain areas. The frequencies of both glutamatergic and GABAergic currents increased abruptly at the beginning of the second postnatal week, supported by a serotonin upsurge. Integrative behaviors arose on postnatal day (P)9, while most motor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
6
36
0
Order By: Relevance
“…We tested the specificity of our construct through immunohistochemistry for somatostatin: 83 ± 8% of cells expressing the inhibitory hM4Di-DREADD also expressed somatostatin (n = 4 animals, Fig 5B) and 79 ± 6% of SST cells expressed the hM4Di-DREADD. We also confirmed that at this age, activation of the hM4Di-DREADD construct with clozapine reduced excitability of DREADD-expressing cells in vitro ( Supplementary Fig 2A) similar to the excitability reducing effect of hM4Di-DREADD activation in developing layer 2/3 pyramidal neurons described previously (Naskar et al, 2019).…”
Section: Somatostatin Cell Suppression Reduce Event Specificitysupporting
confidence: 90%
“…We tested the specificity of our construct through immunohistochemistry for somatostatin: 83 ± 8% of cells expressing the inhibitory hM4Di-DREADD also expressed somatostatin (n = 4 animals, Fig 5B) and 79 ± 6% of SST cells expressed the hM4Di-DREADD. We also confirmed that at this age, activation of the hM4Di-DREADD construct with clozapine reduced excitability of DREADD-expressing cells in vitro ( Supplementary Fig 2A) similar to the excitability reducing effect of hM4Di-DREADD activation in developing layer 2/3 pyramidal neurons described previously (Naskar et al, 2019).…”
Section: Somatostatin Cell Suppression Reduce Event Specificitysupporting
confidence: 90%
“…We specifically inactivated SST + interneurons by using a Cre-dependent inhibitory DREADD delivered by virus injections, which results in 80% of the SST + interneurons expressing the hM4Di-DREADD construct 28 . Bath application of clozapine in vitro reduced the excitability of SST + interneurons 28 , replicating previous findings that hM4Di-DREADD activation reduces the excitability of developing layer 2/3 neurons 36 . We performed in vivo wide-field calcium imaging to monitor spontaneous network activity in V1 and then activated the iDREADD receptor by injecting clozapine subcutaneously (Fig.…”
Section: Oxytocin Modulates Spontaneous Activity Patterns Activatingsupporting
confidence: 87%
“…Also, pyramidal cells in the mouse and ferret visual cortex are already orientation selective at (43) and before (44,45) eye opening, providing another likely source of the synaptic Gabor receptive fields in our model. We find that a rapid increase in spine density during the second postnatal week (60) , which possibly indicates the establishment of dense, intralaminar and intercortical connections (61) , does not disrupt already established synaptic clusters ( Supplementary Fig. 16).…”
Section: Discussionmentioning
confidence: 83%
“…This novel synapse could potentially come from a pool of silent synapses, a type of synapse that lacks AMPA receptors but can become unsilenced through activity-dependent mechanisms (80) . While we maintain a constant density of synapses throughout our simulations, a rapid increase in synaptic density like the one observed during development in the somatosensory cortex (61) does not interfere with the formation of synaptic clustering ( Supplementary Fig. 16).…”
Section: Retinal Wave Generationmentioning
confidence: 95%